Effects of arm swing exercise training on cardiac autonomic modulation, cardiovascular risk factors, and electrolytes in persons aged 60-80 years with prehypertension: A randomized controlled trial - Piyapong Prasertsri; Sanita Singsanan; Chirapond Chonanant; Orachorn Boonla; Petcharat Trongtosak (Elsevier, 2019)
Background/Objective: This study aimed to investigate the effect and carry-over effect of arm swing exercise (ASE) training on cardiac autonomic modulation, cardiovascular risk factors, and blood electrolytes in older persons with prehypertension. Methods: Subjects were 50 individuals with prehypertension (aged 66.90 ± 5.50 yr, body mass index 23.84 ± 3.65 kg/m2). They were randomly assigned into ASE group and control group. Subjects in the ASE group underwent an ASE training program for 3 months at a frequency of 30 min/day, 3 days/week. Subjects in the control group maintained their daily routine activities minus regular exercise. Blood pressure, heart rate variability (HRV), cardiovascular risk factors including blood glucose, lipid profile, high-sensitive C-reactive protein (hsCRP), and electrolytes were evaluated on 3 occasions: before and after the 3-month intervention, and 1 month after intervention ended. Results: Following the 3-month intervention, systolic blood pressure (SBP) and serum hsCRP concentration were significantly lower, while serum high-density lipoprotein (HDL)-cholesterol, potassium (K+), magnesium (Mg2+) concentrations, standard deviation of normal R-R intervals (RMSSD) and high frequency (HF) power values were higher in the ASE group when compared with the control group (p < 0.05). At the 1-month follow-up interval, SBP and serum hsCRP concentration remained lower while serum HDL-cholesterol and K+ concentrations remained higher in the ASE group as compared to the control group (p < 0.05). Conclusion: ASE training decreased SBP and serum hsCRP concentration, increased serum HDL-cholesterol, K+, and Mg2+ concentrations and increased RMSSD and HF power values in older persons with prehypertension. In addition, there were carry-over effects of ASE training i.e. decreased SBP and serum hsCRP concentration as well as increased serum HDL-cholesterol and K+ concentrations. Keywords: Blood pressure, Exercise, Cardiovascular disease, Heart rate variability, Electrolyte